Quatrième génération - Delorme, Wendy (Points, 2022)
« Quatre générations de femmes, quatre générations de féminismes. Une fiction sur le corps, la sexualité et ses potentialités politiques.. Quatre générations de femmes, une « folie » familiale qui se décline au féminin pluriel racontée du point de vue d'une jeune narratrice lucide et ironique sur l'état d'une société qui exclut les marginaux. Car Marion aime les femmes mais pas seulement, c'est plus compliqué que ça, le sexe et le genre. Au fil de ses rencontres amoureuses et sexuelles, on découvre des identités qui déjouent la binarité des rapports masculin et féminin. Raconter l'enfance, les amitiés, les amours queer et le sexe de façon décomplexée, c'est ce qu'entreprend Marion en voyageant de Paris à San Francisco, dans ce texte qui tient du roman, du manifeste et de la chronique d'un univers alternatif. »–Quatrième de couverture.
Section: 258 pages ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; identités LGBTQIA2+; lesbianisme; lit2815; premier cycle; queer; roman; thématiques; études littéraires

Lesbian potentiality and feminist media in the 1970s - Samer, Rox (Duke University Press, 2022)
In Lesbian Potentiality and Feminist Media in the 1970s, Rox Samer explores how 1970s feminists took up the figure of the lesbian in broad attempts to reimagine gender and sexuality. Samer turns to feminist film, video, and science fiction literature, offering a historiographical concept called “lesbian potentiality”—a way of thinking beyond what the lesbian was, in favor of how the lesbian signified what could have come to be. Samer shows how the labor of feminist media workers and fans put lesbian potentiality into movement. They see lesbian potentiality in feminist prison documentaries that theorize the prison industrial complex’s racialized and gendered violence and give image to Black feminist love politics and freedom dreaming. Lesbian potentiality also circulates through the alternative spaces created by feminist science fiction and fantasy fanzines like The Witch and the Chameleon and Janus. It was here that author James Tiptree, Jr./Alice B. Sheldon felt free to do gender differently and inspired many others to do so in turn. Throughout, Samer embraces the perpetual reimagination of “lesbian” and the lesbian’s former futures for the sake of continued, radical world-building.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; cinéma; communication; discipline; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; thématiques; études littéraires